Identification of a novel drug-resistant community-acquired Nocardia spp. in a patient with bronchiectasis. Issue 1 (31st December 2022) - Li, Zhengtu; Li, Yongming; Li, Shaoqiang; Li, Zhun; Mai, Ying; Cheng, Jing; Su, Danhong; Zhan, Yangqing; Zhong, Nanshan; Ye, Feng
ABSTRACT: A previously unknown Nocardia species was isolated from the lung tissue and bronchoalveolar lavage fluid (BALF) of a 58-year-old woman with bronchiectasis and recurrent pneumonia. This Nocardia (GZ2020 T ), which grew readily in Columbia blood agar and could induce pneumonia in a mouse model, represents a novel Nocardia species, and its closest known relatives are Nocardia anaemiae NBRC 100462 T, Nocardia pseudovaccinii NBRC 100343 T and Nocardia vinacea NBRC 16497 T . However, unlike all previously known species, GZ2020 T is the first genus of Nocardia spp. that is not susceptible to multiple drugs but does show susceptibility to linezolid and moxifloxacin, and thus, GZ2020 T potentially represents a substantial health threat to patients with bronchiectasis and immunocompromised individuals. Although the original pathogen source and method of spreading remain uncertain, a mode of transmission from the environment to humans could exist. Vigilance with respect to its spread in the population and the transmission of antibiotic resistance genes in the environment should be maintained.